Students’ Response of Using Cornell Note Taking System (CNTS) in Listening Class - Ahmad Syafi’I (Journal of English Language Teaching and Islamic Integration, 2019)
The  main  concern  of  the  present  study  is  to  investigate  the  students’ response in CNTS in Literal Listening. This study employs descriptive qualitative method. It involves 18 students who enrolled in Literal Listening Class. Data was gathered through questionnaire and interview. The results of the study showed that note taking was still presumably considered as difficult skill because most lecturers were still not familiar to it. Consequently the students often struggle to decide what to note as the lecturers do not tell what to include in note. However, Cornel Note Taking  System  was  generally  proven  helpful  study  tool  in  listening  activity particularly it is because CNTS was a systematic guided note that perceived to be very  helpful  for  students  to  be  a  good  note  taker.  Suggestions  are  proposed  for teacher  particularly  to  prepare  students  with  techniques  of  what  to  note  and instroduce it earlier so that it would become the students’ habit. The results of this study may also be addressed for those who are interested in this field particularly English lecturers or lecturers who have problems in teaching listening.